EVOLUTION OF MEADOW SAZ SOILS OF THE EASTERN PARTS OF THE FERGANA VALLEY UNDER THE INFLUENCE OF ANTHROPOGENIC FACTORS - U. B. Mirzaev; M. I. Kuldasheva (Web of Journals Publishing, 2025)
The article highlights the role of anthropogenic factors in the process of modern evolutionary development of irrigated meadow-saz soils of Eastern Fergana.
Keywords: Anthropogenic factor, morphology, mechanical composition, coarse dust, silt, fine sand, evolutionary development, arzik, shoh, gypsum, carbonate, easily soluble salts.